A Survival Analysis of Invasive Fungal Diseases in Children with Cancer - Marques, Letícia Maria Acioli; de Araujo, Orlei Ribeiro; de Sousa da Silva, Adriana Maria Paixão; da Silva, Dafne Cardoso Bourguignon; Carlesse, Fabianne Altruda de Moraes Costa (Journal of Pediatric Infectious Diseases, 2021)
Objective This study aimed to determine the survival in a retrospective cohort of 152 patients treated for invasive fungal diseases (IFD) (133 proven and 19 probable) in 9 years.Methods Our study included patients aged 0 to 18 years diagnosed with cancer at our institution and with proven or probable IFD, treated from 2011 to 2019. Weibull distribution was used for hazard ratios and accelerated failure time models for the outcome “death attributed to IFD.”Results Our median age was 97 months. The most frequent diagnosis was leukemia (39, 25.7%). A total of 37 patients received prophylaxis with fluconazole (24.3%). Among 133 fungal isolates, the most frequent were Candida species in blood 81 (53.2%). Moreover, 43 deaths were attributed to IFD (28.3%). Survival probabilities were lower for pulmonary IFD (46.9%, p = 0.0017), leukemia (62.5%, p = 0.004), and neutropenia <500 cells/mm3 (55.4%, p < 0.0001). For Candida fungemia, survival probabilities were 76.6% (p = 0.043). In Weibull models, the diagnosis of leukemia shortened survival times by a factor of 0.006, relapse of disease by 0.05, lymphoma by 0.04, pulmonary IFD by 0.04, and neutropenia by 0.015. Hematopoietic stem cell transplantation did not affect the survival times as well as prophylaxis with fluconazole.Conclusion Host factors, such as neutropenia, relapse of disease, and hematologic malignancies, are determinants in the survival times of children with IFD as well as pulmonary involvement.
Keywords: fungi; cancer; survival analysis